Parafoveal Processing in Chinese Sentence Reading: Early Extraction of Radical Level Phonology - Luo, Jiefei; Wu, Yan; Jiao, Runkai (Frontiers in Psychology, 2018)
In the field of reading comprehension, one of the most controversial issues is whether phonological codes can be activated and then affects current processing. Current study explored this issue by observing the effects of phonogram regularity in Chinese sentence reading when eye movement was recorded. To be specific, critical phonetic radicals were inserted into the sentences as target characters. The boundary paradigm was used such that when their eyes crossed an invisible boundary location, a preview character changed to the target character. In Experiment 1, the preview could either be a regular phonogram (清 /qing1/ as a preview for 青 /qing1/), an irregular phonogram (猜 /cai1/ as a preview for 青 /qing1/), a homophone of the target character (轻 /qing1/ as a preview for 青 /qing1/), or an unrelated control character (洋 /yang2/ as a preview for 青 /qing1/). In Experiment 2, the irregular previews were replaced by the semi-regular phonograms (精 /jing1/), while the other conditions were kept the same. Results showed that readers obtained preview effects only from the regular phonograms but not the irregular or semi-regular ones at the initial processing stage. But in the later stage, phonetic radicals in all types of phonograms could be previewed and then to influence current processing. This indicates that the phonological cue provided by phonetic radicals could play an early role in Chinese text reading and phonogram regularity is the necessary information to facilitate Chinese word processing at the initial processing stage, at the same time there have a strong and stable orthographic preview effect in the entire processing stage.